Novel Nanotechnological Approaches for Targeting Dorsal Root Ganglion (DRG) in Mitigating Diabetic Neuropathic Pain (DNP) - Bhandari, Ranjana; Sharma, Ashmita; Kuhad, Anurag (Frontiers in Endocrinology, 2022)
Diabetic neuropathy is the most entrenched complication of diabetes. Usually, it affects the distal foot and toes, which then gradually approach the lower part of the legs. Diabetic foot ulcer (DFU) could be one of the worst complications of diabetes mellitus. Long-term diabetes leads to hyperglycemia, which is considered to be the utmost contributor to neuropathic pain. Hyperglycemia causing upregulation of voltage-gated sodium channels in DRG was often observed in models of neuropathic pain. DRG opening frequency increases to increase intracellular sodium ion levels, which further causes increased calcium channel opening and stimulates other pathways leading to DPN. Currently, pain due to diabetic neuropathy is maintained via antidepressants, opioids, GABA analogs, and topical agents like capsaicin. Despite the availability of various treatment strategies, the percentage of patients achieving adequate pain relief remains low. Many factors contribute to this condition, like lack of specificity and adverse effects like light-headedness, languid, and multiple daily doses. Therefore, nanotechnology outperforms in every aspect to provide several benefits compared to traditional therapy like site-specific and targeted drug delivery. Nanotechnology is the branch of science that deals with the development of nanoscale materials and products, even smaller than 100nm. By incorporating drugs into the novel, carriers can improve their efficacy with reduced side effects. Thus, the utilization of nanotechnological approaches such as nanoparticles, polymeric nanoparticles, inorganic nanoparticles, lipid nanoparticles, gene therapy (siRNA and miRNA), and extracellular vesicles can extensively contribute to relieving neuropathic pain.